Sistem Pendukung Keputusan Seleksi Penerima Beasiswa KIP Kuliah Menggunakan Metode SAW dengan Pembobotan Kriteria Akademik dan Kondisi Ekonomi Mahasiswa - Laura; Yaslinda Lizar (Jurnal Informatika & Teknologi Cerdas, 2026)
The scholarship recipient selection process requires an assessment mechanism capable of accommodating multiple criteria in a fair and measurable manner. The large number of applicants and the variety of factors considered often make the selection process complex when conducted manually. Such conditions may lead to subjectivity and inconsistencies in decision-making. This study aims to develop a Decision Support System (DSS) to assist in selecting scholarship recipients by applying the Simple Additive Weighting (SAW) method. The SAW method was chosen because it can process multiple criteria that have been assigned weights according to their level of importance, thereby generating preference values that can be used as the basis for determining scholarship recipients. The criteria used in this study include Grade Point Average (GPA), parents’ income, number of dependents in the family, student achievements, and attendance records. Data were collected through the distribution of questionnaires to 30 respondents to obtain information regarding the relevance and importance of each criterion. The results indicate that the implementation of the SAW method can systematically rank scholarship candidates based on the highest preference values. Therefore, the developed system can support a more efficient, objective, and accountable scholarship selection process.